(3bUI Mi Hf jbXGfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3Mi Hf jbXGf eG Mi GHf jbXGf SHMGf ehMO PGc GdTjN SHMGfG s
(3BNQgG (B:s
(3dGTF CdWa efgG Gf ef YQa GdbOje GUai LejY GdNdb GQOfGgG JeJ GdbUjOI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOS YTQs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1327s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdadSaI hGdefWbs